1985
DOI: 10.1063/1.96266
|View full text |Cite
|
Sign up to set email alerts
|

A 19% efficient AlGaAs solar cell with graded band gap

Abstract: An Al0.20Ga0.80As solar cell with a band gap graded from 1.64 eV at the junction to 1.72 eV at the surface has been fabricated using metalorganic chemical vapor deposition. An efficiency of 19.2% has been measured under 1-sun, AM2 simulated conditions with an open circuit voltage of 1.18 V, a short circuit density of 14.5 mA/cm2, and a fill factor of 0.83.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 2 publications
0
11
0
Order By: Relevance
“…The design is technologically feasible, as it has been shown that graded In x Ga 1 À x N layers can be grown over the entire composition range using the Energetic Neutral Atom Beam Lithography and Epitaxy (ENABLE) process [20]. Compositional grading in solar cells has previously been considered in the Al x Ga 1 À x As materials system, where it was found to reduce surface recombination losses [21,22]. Grading has also been used in CuIn x Ga 1 À x Se 2 cells to increase the efficiencies in thin devices [23].…”
Section: Introductionmentioning
confidence: 98%
“…The design is technologically feasible, as it has been shown that graded In x Ga 1 À x N layers can be grown over the entire composition range using the Energetic Neutral Atom Beam Lithography and Epitaxy (ENABLE) process [20]. Compositional grading in solar cells has previously been considered in the Al x Ga 1 À x As materials system, where it was found to reduce surface recombination losses [21,22]. Grading has also been used in CuIn x Ga 1 À x Se 2 cells to increase the efficiencies in thin devices [23].…”
Section: Introductionmentioning
confidence: 98%
“…These are listed in Table . We also calculated the EREs of III–V/Si and III–V solar cells in using this approach. The results are listed in Table .…”
Section: External Radiative Efficiencies Of State‐of‐the Art Iii/v Onmentioning
confidence: 99%
“…These are listed in Table I. We also calculated the EREs of III-V/Si and III-V solar cells in [15][16][17] using this approach. The results are listed in Table II.…”
Section: External Radiative Efficiencies Of State-of-the Art Iii/v Onmentioning
confidence: 99%
“…With these ERE values of each subcell, the limiting efficiency of this 2J cell is 36.5%. Because achieving the quality of state-of-the-art GaAs is still challenging for the candidate 1.73-eV III-V materials, a more realistic estimate is considering a top cell that matches the EREs of the AlGaAs reported in [15] or [16], which are both around 10 -4 . The limiting efficiency of this 2J cell is then 33.9%.…”
Section: Design Considerations Of Iii-v/si Solar Cellsmentioning
confidence: 99%